Assessing the Impact of Landcover Change on Soil Organic Carbon Stocks in Chile: Implications for Terrestrial Ecosystems and Conservation Policies - Alaniz-Baeza, A (John Wiley and Sons Inc, 2025)
Understanding soil organic carbon (SOC) dynamics is crucial for understanding the global carbon cycle and ensuring soil and terrestrial ecosystems function. This study provides a comprehensive assessment of SOC distribution across terrestrial ecosystems and protected areas in Chile, focusing on the interactions between land cover (LC) types and their impacts on SOC stocks (SOCs), aiming to evaluate current SOC degradation and inform conservation strategies. To analyse topsoil (0–30 cm) SOC content (%) and SOCs across LC categories defined as low-intensity LC (minimally impacted by human activities) and ‘high-intensity LC’ (substantially impacted by human activities). A Random Forest modelling approach was used, integrating remote sensing environmental variable data from Landsat 8, MODIS and SRTM topography, along with over 12,000 presence points compiled from literature and unpublished datasets. Chilean ecosystems contain approximately 1.37 pg of SOCs, with nearly 80% in low-intensity LC and temperate forests, highlighting their importance in carbon conservation. Vulnerable ecosystems, such as Sclerophyllous Forests, retain only 45% of their original stock and have experienced 10% fire damage in the last decade. The present assessment of SOC levels in protected areas highlights the importance of public lands in conserving SOC, as they contain over six times more SOC than private areas and are predominantly present within the low-intensity LC. However, important conservation gaps are still present, as ecosystems such as deciduous forests, steppes & grasslands and thorny shrublands, which together store nearly 40% of the national SOC stock, are not currently under the protected area network. These results are key to understanding the dynamics of soil SOC in heterogeneous landscapes and emphasize the need to align conservation strategies with carbon storage priorities. Synthesis and applications. Our study identifies key implications for in situ conservation efforts by pinpointing threatened ecosystems and addressing gaps in soil protection through the improvement or expansion of protected areas to face a world-changing climate. It provides valuable inputs for modelling areas prone to soil degradation and irreplaceable soil organic carbon loss. These insights are crucial for shaping national and international evidence-based policies and improving conservation and restoration initiatives. © 2025 The Author(s). Journal of Applied Ecology © 2025 British Ecological Society.